The impact of technology-enhanced organisational learning on business performance: An empirical study - Tanja Arh; Borka Jerman Blaézic; Vlado Dimovski (Journal for East European Management Studies, 2012)
This paper focuses on a presentation of the conceptualization of a structural model that was developed to examine the impact of technology-enhanced learning and organizational learning on the business performance of some Slovenian companies with more than 50 employees. In accordance with the stakeholder theory and balanced scorecard (BSC), both the financial and nonfinancial aspects of the performance are considered. The results of the study indicate the strong impact of technology-enhanced learning on organizational learning and non-financial business performance. – – Im Mittelpunkt des vorliegenden Beitrages steht die Präsentation der Konzeptualisierung eines strukturellen Modells, das entwickelt wurde, um die Auswirkung von technologisch unterstütztem und organisiertem Lernen auf den Unternehmenserfolg slowenischer Firmen mit mehr als 50 Beschäftigten zu testen. Gemäß der Stakeholder-Theorie und der Balanced-Scorecard-Methode (BSC), werden sowohl finanzielle als auch nicht-finanzielle Erfolgsaspekte berücksichtigt. Die Ergebnisse der Studie zeigen eine starke Auswirkung des technologisch unterstützten Lernens auf das organisatorische Lernen und auf den nicht-finanziellen Unternehmenserfolg.
Keywords: 650; organizational learning; business performance; research model; LISREL